Military masculinity and postwar recovery in the Soviet Union - Fraser, Erica L. 1976- (University of Toronto Press, 2019)
Rearming Masculinity explores military masculinity in the Soviet Union after the catastrophe of the Second World War. Soldiering had to be reimagined and resold to the public, which involved writing women out and re-establishing military identity as the premier form of masculinity in Soviet society.